HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTUKAN OTOT PUNGGUNG DENGAN HASIL TOLAK PELURU PADA MAHASISWA PUTRA PENDIDIKAN KEPELATIHAN OLAHRAGA 2013 UNIVERSITAS RIAU - Friska '; Slamet '; Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this study originated from the observation that the author found in the field that researchers encounter deficiencies during repulsion is still a lack of muscle strength and flexibility shoulder arm back muscles at the time rejected the resulting proceeds are less than the maximum repulsion. The purpose of this research was to determine the relationship of the shoulder and arm muscle strength of the back muscles flexibility with shot put results in sports coaching education male students in 2013 University of Riau. The samples in this study is not complete, or do not cover the entire study population, but only a portion of the population alone. Researchers took a sampling technique focuses on purposive sampling technique. To obtain research data used Expanding Dynamometer tests for shoulder arm muscle strength, test Sit and Rise to the back muscle flexibility, and refused bullet for the shot put. Data were analyzed with a simple product moment correlation. Based on the analysis of data obtained correlation X1 with Y for rhitung = 0,713˃rtabel = 0.404 and X2 with Y for rhitung = 0,719˃rtabel = 0.404 while the X1 and X2 with Y rhitung = 0,599˃rtabel = 0.404. Because of all the relationships shown in data analysis is significant, it is thus Ha Ho accepted and rejected. Where the provisions of the correlation of a correlation of a variable with other variables determined from rhitung rtabel.Keywords : Shoulder Arm Muscle Strength, Muscle flexibility Backs, Reject                 Bullet